The Effect Of E-Filing Implementation, Tax Socialization, Taxpayer Awareness, And Tax Sanctions On Compliance Individual Taxpayer - Tjokorda Istri Agung Lita Apriliana DEWI; Putu Gede Wisnu Permana KAWISANA; I Gusti Agung Prama YOGA (Indonesia Strategic Sustainability, 2022)
This study aims to determine the effect of the implementation of e-Filing, tax socialization, taxpayer awareness and tax sanctions partially and simultaneously on individual taxpayer compliance. The location of this research is at the East Denpasar Primary Tax Service Office. The population uses individual taxpayers at the East Denpasar Pratama Tax Service Office and a sample of 100 respondents. The data analysis technique uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F Test and t Test. From the research results, the results obtained are: (1) the effect of the application of e-Filing has a positive and insignificant effect, where the t count is 1.268 and the significance value is 0.208. (2) tax socialization has a positive and insignificant effect, where the obtained t value of 0.131 and a significance value of 0.896. (3) taxpayer awareness has a significant positive effect on individual taxpayer compliance, where the t-count value is 3.138 and a significance value of 0.002. (4) tax sanctions have a significant positive effect on individual taxpayer compliance, where the t value is 5.586 and a significance value of 0.000. The magnitude of the influence of independent variables on individual taxpayer compliance is 58.4%.